Investigating Earthquake Resistance School Building in Peninsular Malaysia - Wai Yie, Leong; Kok Wah, Choo; Zainab Nik, Nik (International Journal of Engineering and Technology, 2019)
The data sources of earthquake from Off the West Coast of Northern Sumatra and Southern Sumatra with magnitude 9.11 for subduction zone and 7.81 for fault zone were investigated. Based on the previous record, Malaysia has not experienced any major earthquake disasters should not be used as an argument to dismiss the need for taking any pro-active steps to look into the earthquake threat. The purpose of this paper is mainly to identify attenuation equation and response spectrum of bedrock, and to determine performance of building with different response spectrum. Most of the attenuation equations are suitable for distance from source to location below 200 km. The attenuation equations were applied to the data obtained from on the closest location from Sumatra to Malaysia is approximately 340km. Based on the analysis, the performance of building with different combination loads and response spectrum on bedrock would affect the shear force, axial force and moment values of the structural elements. The axial force of structure in Kuala Lumpur with fault zone mechanism, increases about 0.75 percent while shear force for beam 2, it increases by 1.4 percent. The moment reaction increases about 15.07 percents while the moment for increases approximately by 4.70 percent. However, the results for both combination loads are still within the capacity level of the structure. The possible factors that affect the result for this research are the ground motion should consider the soils layers and for more accurate analysis, the structure should be analyzed in nonlinear analysis.Â Â